Examination of medical student and physician attitudes towards suicide reveals need for required training - Schulz, Paulyna; Zapata, Isain; Huzij, Teodor (Frontiers in Public Health, 2024)
The attitudes of healthcare providers towards suicidal patients are known to influence their motivation to treat patients during a suicidal crisis. Patients who attempted suicide are more likely to have recently visited a primary care provider who is not necessarily sufficiently trained in managing a suicidal patient rather than a mental health provider who is trained to do so. For those reasons, documenting medical students and physicians’ attitudes towards suicide can help in the development of effective intervention training to prepare them to manage these types of patients. In this mini review, attitudes towards suicidal patients, the effectiveness of training on changing their attitudes are discussed. In summary, primary care providers are recognized as a top area where improvements can prevent suicides; providing proper suicide prevention training can effectively improve attitudes and quality of care for suicidal patients.